MANAJEMEN LABA, PERTUMBUHAN ASET, RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR RITEL DI INDONESIA - Amrie Firmansyah; Enrico Adhanur Karyadi; Hany Sukma Setyaningtyas (Universitas Jember, 2020)
This study aims to examine the effect of earnings management and company asset growth on stock returns. This research uses quantitative methods with panel data regression. This study's sample uses financial data for retail companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2019. The research sample was selected based on the purposive sampling method of 40 observations. This study concludes that earnings management and asset growth have a positive effect on stock returns. This study shows that the company carries out earnings management for efficiency measures in meeting investor expectations. Also, the company's assets' growth is a positive signal for investors in making investment decisions.Keywords: asset growth, earnings management, firm size, stock return